REVEALING THE INFLUENCE OF DIGITAL LITERACY ON THE INNOVATIVE PERFOMANCE OF MSMEs: THE ROLE OF ENTREPRENEURIAL SKILLS AS A MEDIATING VARIABLE - Nuruliza, Safira; Suparno; Pratama, Aditya (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This research was conducted to analyze the effect of digital literacy on Micro, Small and Medium Enterprises (MSMEs) innovative performance in the culinary sectors in the Jakarta area mediated by entrepreneurial skills. This research uses a method of survey in the forms of primary data by disseminating questionnaires to MSMEs entrepreneur in the culinary sector in Jakarta. In testing this research using SEM analysis techniques with Partial Least Square (PLS). The research results show that digital literacy has a positive and significant influence on the innovative performance of MSMEs in the culinary sector directly by 0.443. Furthermore, digital literacy also has a positive and significant effect on the entrepreneurship skills of MSMEs players in the culinary sector directly by 0.648. Entrepreneurial skills have a significant positive effect on the innovative performance of MSMEs in the culinary sector directly by 0.466. Furthermore, there is an indirect significant positive effect of digital literacy on the innovative performance of MSMEs with the entrepreneurial skills as a mediation variable of 0.302.